Effect of high-intensity interval training on cardiorespiratory in children and adolescents with overweight or obesity: a meta-analysis of randomized controlled trials - Deng, Yiran; Wang, Xianliang (Frontiers in Public Health, 2024)
Objective: This meta-analysis aimed to examine the effect of high-intensity interval training on cardiorespiratory fitness in children and adolescents with overweight or obesity, and to explore the optimal dose of high-intensity interval training to improve cardiorespiratory fitness in children and adolescents with overweight or obesity.Methods: Randomized controlled trials on the effects of HIIT on cardiorespiratory fitness in children and adolescents with overweight or obesity were retrieved from six electronic databases, including PubMed, Web of Science, Cochrane Library, CNKI, Wanfang, and VIP. The quality assessment of the included studies was conducted following the revised quality evaluation method based on the PRISMA principles. Keywords for literature search mainly include high-intensity interval, cardiorespiratory fitness, overweight, obese, children, and adolescent, etc.Results: 1) A total of 18 studies, comprising 581 participants (288 in the intervention group and 293 in the control group), were included and all of them were of moderate to high quality. 2) HIIT had a positive effect on the cardiorespiratory fitness levels of in children and adolescents with overweight or obesity (SMD=0.91; 95% CI: 0.66, 1.15; P<0.00001). 3) The improvement in cardiorespiratory fitness was more significant when the HIIT intervention lasted for more than 10 weeks (SMD=1.04; 95% CI: 0.74, 1.34; P<0.00001), was conducted 3 times per week, with 2 to 8 sets per session (SMD=1.13; 95% CI: 0.71, 1.55; P<0.00001), and maintained a ratio of approximately 1:1 between exercise and rest intervals (SMD=1.11; 95% CI: 0.73, 1.50; P<0.00001).1) Long-term HIIT can improve cardiorespiratory fitness in children and adolescents with overweight or obesity. 2) To achieve significant improvements in cardiorespiratory fitness in a short period, children and adolescents with overweight or obesity can engage in HIIT programs lasting for more than 10 weeks, conducted 3 times per week, with 2 to 8 sets per session, and a ratio of approximately 1:1 between exercise and rest intervals.